Local buckling requirements of carbon cold-formed circular hollow steel sections of mild-to-high strength steel - Dundu, M. (Journal of Structural Engineering, 2024)
This paper assesses the current local buckling requirements of carbon cold-formed steel hollow sections under axialcompression, using data from literature. A total of 39 Circular Hollow Steel Sections (CHSSs) are analysed, and theseinclude 19 columns of mild steel and 20 columns of high strength steel. Variables in the study includes the length,diameter, thickness and material properties. The outside diameter-to-thickness ratio (d/t) for CHSSs of mild steelranged from 48.72 to 249.23, while the outside diameter-to-thickness ratio (d/t) for CHSSs of high strength steel rangedfrom 16.15 to 46.84. The corresponding yield stress for mild steel ranged from 203.80 MPa to 622.80 MPa, while that ofhigh strength steel ranged from 1341.00 MPa to 1405.00 MPa. A comparison with CAN/CSA-S16-09 and EN 1993-1-1,shows the limits of both standards to be too conservative. New slenderness limits are proposed to improve the designof these sections.